2017
DOI: 10.1038/s41598-017-11951-1
|View full text |Cite
|
Sign up to set email alerts
|

The Homologous Recombination Machinery Orchestrates Post-replication DNA Repair During Self-renewal of Mouse Embryonic Stem Cells

Abstract: Embryonic stem (ES) cells require homologous recombination (HR) to cope with genomic instability caused during self-renewal. Here, we report expression dynamics and localization of endogenous HR factors in DNA break repair of ES cells. In addition, we analyzed gene expression patterns of HR-related factors at the transcript level with RNA-sequencing experiments. We showed that ES cells constitutively expressed diverse HR proteins throughout the cell cycle and that HR protein expression was not significantly ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…More precisely, regulation of the recombinases RAD51, RAD52, and RAD54 has been shown to affect genomic integrity and regulation of the cell cycle. Our results demonstrated that cells lacking RAD51 experienced cell cycle arrest in the G2/M phase and the accumulation of DNA breaks, apoptosis, and unrepaired ssDNA, implying that the HR factor-dependent pathway is likely essential for the maintenance of genomic integrity 35 .…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…More precisely, regulation of the recombinases RAD51, RAD52, and RAD54 has been shown to affect genomic integrity and regulation of the cell cycle. Our results demonstrated that cells lacking RAD51 experienced cell cycle arrest in the G2/M phase and the accumulation of DNA breaks, apoptosis, and unrepaired ssDNA, implying that the HR factor-dependent pathway is likely essential for the maintenance of genomic integrity 35 .…”
Section: Discussionmentioning
confidence: 72%
“…The transcription factor E2F1 is involved in DNA replication and repair in many types of human cancers 38 . Previous studies have reported that E2F1 is expressed at high levels in most human cancers, including colon cancer and breast cancer and that E2F1 expression in an individual cell facilitates the efficient repair of DSBs and stalled replication forks 35,39 . However, the reason for high-level E2F1 expression in human cancer cells and the specific role of E2F1 in maintaining genomic integrity in cancerous cells are not clearly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though ES cells lack a robust innate immune system, they are nonetheless hypersensitive to DNA damage and readily undergo differentiation and apoptosis ( 8587 ). This is not due to a diminished DNA repair capacity because many repair-related factors are in fact elevated in ES cells ( 8890 ). Taken together, these observations suggest that alternative mechanisms likely exist in order to sensitize ES cells to these cellular insults, thereby protecting the pristine state of ES cells from infections and genome instability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because Myst2 accelerates cell proliferation [17], we checked the function of Myst2 on cell-cycle progression in mESCs. The transition from G1 phase to S phase was blocked by treatment with double thymidine and then the cell-cycle progression was released as previously described [18] (Fig. 7c).…”
Section: Regulation Of Myst2 By Huwe1-brpf3 Is Involved In Cellular Rmentioning
confidence: 99%